2018
DOI: 10.31298/sl.142.7-8.2
|View full text |Cite
|
Sign up to set email alerts
|

Zalihe biomase mrtvog drva u šumskim ekosustavima bukve (Fagus sylvatica L.) na području zapadnog Balkana, Bugarska

Abstract: SUMMARYThe dead trees play an important role in the functioning and productivity of the forests' ecosystems through influence over biological diversity, the accumulation of carbon dioxide, nutrient turnover and energy flux, hydrological processes, protection of the soils and the regeneration of tree species. The dead wood assures important habitats also. In historical aspect, for many years the dead wood was removed from the stands as a measure for protection against insects and fungi, which are perceived as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Studies on the AGB and CS in relation to other variables, such as altitude, are crucial for understanding the importance of virgin forests in slowing global warming. Our research, along with other studies [27,62,70], highlights that the DW biomass decreases with altitude and, implicitly, with air temperature [69].…”
Section: Descriptive Statisticssupporting
confidence: 77%
See 1 more Smart Citation
“…Studies on the AGB and CS in relation to other variables, such as altitude, are crucial for understanding the importance of virgin forests in slowing global warming. Our research, along with other studies [27,62,70], highlights that the DW biomass decreases with altitude and, implicitly, with air temperature [69].…”
Section: Descriptive Statisticssupporting
confidence: 77%
“…The relationship between DW and living tree volumes has been highlighted previously [27,62], and recent studies performed in virgin forests in the Semenic Mountains (Southern Carpathians) have shown that the volume of dead wood there varied between 50 m 3 •ha −1 and 223 m 3 •ha −1 [21].…”
Section: Descriptive Statisticsmentioning
confidence: 99%